THE IMPLEMENTATION OF PROJECT BASED LEARNING TO IMPROVE STUDENT’S SPEAKING SKILL - Haerani, Rini; Jatiraga, Rahayu (PROJECT (Professional Journal of English Education), 2019)
The background of the experiment was to find out whether the influence of project based learning in improving the speaking skill among eighth grade students of SMPN 3 Padalarang in the academic year of 2018/2019. The method of this study was quantitative technique and the one shot case study design conducted in single class. The researcher conducted the tests before (pre-test) and after (post-test). The research effect display the improvements in speaking ability. The score of pre-test was 63.87, and the post-test was 76.29. Based on students’ attitudes toward the utilized Project based learning, the discovery indicated that most of students rated the use of technique moderately positive. Nearly all of students agreed that project based learning is capabel to improve their speaking mastery ,accumulate their vocabulary mastery,develop their creative thinking, and increase their presentation skill. issue of this study showed that by applying project based learning on learning English can to increase students’speaking skill.Keywords: project based learning, speaking skill